Semantic and Stylistic Peculiarities of Compound Words in Lesia Ukrainka’s Poetry (Linguostylistic Studies, 2014)
The article is devoted to the analysis of traditional and individually-author compound words in Lesia Ukrainka’s poetry. The criteria that qualify used in the artistic texts compound words as author lexical neologisms have been given. The results of statistic research of writer’s poetic texts for ascertainment of frequency of compound words have been given. The most used traditional compound words characterizing different semantic objects in Lesia Ukrainka’s texts have been researched; the folklore units that poetess use as the style created means have been described. The semantics of author compound words that fixed in Lesia Ukrainka’s and Taras Shevchenko’s poetries has been compared. Proved, that Lesia Ukrainka continues and develops beginning by T. Shevchenko tradition of stylistic using of compound words in the artistic texts. Concluded, that compound nominations functionate as original rhymes, emotion and expressive means of figurative word nomination. Key words: compound word, author lexical neologism, folklore word, apposition, Ukrainian poetry of XIX century, T. G. Shevchenko, Lesia Ukrainka. References